Effects of potentilla discolor bunge extracts on oxidative stress and glycolipid metabolism in animal models of diabetes: a systematic review and meta-analysis - Yang, Yunjiao; Deng, Wen; Wu, Yue; Zi, Changyan; Chen, Qiu (Frontiers in Pharmacology, 2023)
Background/aim: Potentilla discolor Bunge (PDB) is an ancient herb of traditional Chinese medicine. Studies have suggested that extracts of PDB may ameliorate diabetes mellitus (DM). This study aimed to systematically assess the efficacy of PDB extracts on glycolipid metabolism and oxidative stress in animal models of diabetes and to provide evidence-based references for the use of PDB extracts. Methods: This study followed the PRISMA 2020 guidelines. Studies were searched from eight databases until January 2023. Statistical analysis was performed using StataSE 15.0 and RevMan 5.3. The standard mean difference (SMD) and 95% confidence intervals (CI) were computed using the random-effects model. SYRCLE's risk of bias tool was used to assess the risk of bias. Results: In total, 32 studies with 574 animals were included. The findings demonstrated that PDB extracts considerably lowered fasting blood glucose (SMD: -3.56, 95%CI: -4.40 to -2.72, p<0.00001); insulin resistance (SMD: -3.19, 95% CI: -5.46 to -0.92, P =0.006), total cholesterol (SMD: -2.18, 95%CI: -2.89 to -1.46, P<0.00001), triglyceride (SMD: -1.48, 95% CI: -2.01 to -0.96, P<0.00001), low-density lipoprotein cholesterol (SMD: -1.80, 95% CI: -2.58 to -1.02], P<0.00001), malondialdehyde (SMD: -3.46, 95% CI: -4.64 to -2.29, P<0.00001) and free fatty acid levels (SMD: -3.25, 95%CI:-5.33 to -1.16, P=0.002), meanwhile, increased insulin sensitivity index (SMD: 2.51 95% CI: 1.10 to 3.92, P= 0.0005), body weight (SMD:1.20, 95% CI: 0.38 to 2.01, P=0.004), and the levels of high-density lipoprotein cholesterol (SMD: 1.04, 95% CI: 0.40 to 1.69, P=0.001), superoxide dismutase (SMD:2.63, 95% CI: 1.53 to 3.73, P<0.00001), glutathione peroxidase (SMD:1.13, 95%CI: 0.42 to1.83, P=0.002), and catalase (SMD:0.75, 95% CI: 0.11 to 1.40], P=0.02). Conclusion: These findings suggest that PDB extracts can ameliorate DM by improving glycolipid metabolism and oxidative stress. PDB may be a promising medication for DM; however, due to significant heterogeneity between studies, these findings should be interpreted with caution. In addition, future well-designed trials should determine which components of the PDB play a major role in ameliorating DM and whether these benefits persist in humans.